2000
DOI: 10.1034/j.1399-3003.2000.15d22.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-alpha production in human alveolar macrophages: modulation by inhaled corticosteroid

Abstract: Using an ex vivo alveolar macrophage model, the hypothesis that inhaled preparations of corticosteroids might have important anti-inflammatory effects on cells of the peripheral airway was tested.The tumour necrosis factor (TNF)-a-inducing potential of three glycolipid preparations from nonpathogenic (arabinofuranasyl lipoarabinomannan (LAM (Ara-LAM)) and virulent (mannase LAM (ManLAM)) mycobacteria and Gram-negative bacteria (lipopolysaccharide (LPS)), in primary alveolar macrophage preparations was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…10 However, when comparing the effect of half dose HFA-BDP with budesonide delivered from a dry powder inhaler, 6,15 end-expiratory flow improvements were found to be similar for both. Busse et al 16 reported a shift to the left of the HFA-BDP versus the CFC-BDP doseresponse curve for forced expiratory flow between exhalation of 25% and 75% forced vital capacity (FEF 18 have shown a greater potential for an anti-inflammatory effect on an ex vivo alveolar macrophage preparation when inhaled steroids had been delivered via HFA-BDP versus CFC-BDP aerosols, the functional benefit of the acinar airways peripheral to the first 150 mL of conductive airways has never been assessed. With the low resistance of the acinar lung zone impeding conventional spirometry to provide a noninvasive marker of the acinar lung structure, ventilation distribution tests offer a valuable alternative.…”
mentioning
confidence: 98%
“…10 However, when comparing the effect of half dose HFA-BDP with budesonide delivered from a dry powder inhaler, 6,15 end-expiratory flow improvements were found to be similar for both. Busse et al 16 reported a shift to the left of the HFA-BDP versus the CFC-BDP doseresponse curve for forced expiratory flow between exhalation of 25% and 75% forced vital capacity (FEF 18 have shown a greater potential for an anti-inflammatory effect on an ex vivo alveolar macrophage preparation when inhaled steroids had been delivered via HFA-BDP versus CFC-BDP aerosols, the functional benefit of the acinar airways peripheral to the first 150 mL of conductive airways has never been assessed. With the low resistance of the acinar lung zone impeding conventional spirometry to provide a noninvasive marker of the acinar lung structure, ventilation distribution tests offer a valuable alternative.…”
mentioning
confidence: 98%
“…Although inhalation of free GC is a promising therapy with less systemic toxicity, the therapeutic efficacy has been ques-tioned with regard to its short half-life (O'Byrne and Pedersen, 1998), potential toxicity at high doses (Foster et al, 2006), and inability to reach alveolar macrophages (Marshall et al, 2000). For these reasons, aerosol drug delivery systems need to be developed.…”
Section: Inhalation Of Lipopolysaccharide (Lps)mentioning
confidence: 99%
“…Causal relationships between the sites of drug deposition and the patients' response have been established in diseases of the respiratory tract [235], but no data exist for cystic fibrosis. Effective targeting of a given region in the lung, for instance the peripheral airways, has been defined when N 50% of the total drug deposition occurs in that region [197,144].…”
Section: Deposition Pattern and Breathing Patternmentioning
confidence: 99%